Evaluation of the role of the hystrosalpingography in prediction of endometriosis in infertile females - Said, Tamer H.; Shehata, Gehan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Hysterosalpingography is the testing the patency of the tubes and the uterine cavity by injecting urographin inside them. The purpose in this study was to evaluate 2 signs in hysterosalpingography (higher position of one or both tubes and S or C shape in the course of one or both tubes) in prediction of endometriosis. Methods: This was prospective cohort study that was done in El-Shatby Maternity University Hospital, Alexandria University. The study included eighty six infertile women who were assigned to do laparoscopy. Recent hysterosalpingography was done within 3 months period before laparoscopy and comments were done on the position and S or C shape in the course of the tube then laparoscopy was done and document all findings including presence of endometriosis and biopsy was taken from atypical lesions. Results: All signs show high specificity in prediction of endometriosis although only 2 signs (higher level of left tube and bilateral tubal S or C shape) showed significantly high sensitivity in prediction of endometriosis. Conclusion: Careful examination of the HSG film and searching for the specific signs of endometriosis is a practical and simple method in prediction of endometriosis. These preliminary data suggest that HSG has a role in prediction of endometriosis.